Borboletas como indicadores biológicos de diversidade, no município de Belém, Pará - Silva, Paula Joseanny Borges da (Museu Paraense Emílio Goeldi, 2023)
Studies on butterflies in Belém are fragmented and sometimes taxonomically obsolete, even for the most studied groups. Currently, nature has been drastically modified by man, which has caused changes in the basic living conditions of these animals, leading to extinction of species, since this group of animals shows quick and typical reactions to different types and levels of environmental disturbance (Brown 1991, 1996a, 1997a,b), thus being good indicator groups for monitoring. Collections of adult individuals continued to be made in 2000 at various points around the city, with the goal of making the documentation of the species more complete for the municipality of Belém. This work was specifically directed at three families: Pieridae, Papilionidae and Nymphalidae, which constitute the PPN group. Comparing data on the abundance of butterflies in Belém in the past, it is clear the decline of its population, a direct consequence of increasing urbanization that increasingly restricts the habitat, in view of these observations, the order Lepidoptera constitutes a group that due to its great fragility can be considered powerful bio-indicators, which proves its importance and urgent need for the preservation of these insects.